Long Non-Coding RNA PCAT6 Induces M2 Polarization of Macrophages in Cholangiocarcinoma via Modulating miR-326 and RhoA-ROCK Signaling Pathway - Tu, Jianfei; Wu, Fazong; Chen, Li; Zheng, Liyun; Yang, Yang; Ying, Xihui; Song, Jingjing; Chen, Chunmiao; Hu, Xianghua; Zhao, Zhongwei; Ji, Jiansong (Frontiers in Oncology, 2021)
LncRNAs can act crucial roles in multiple tumors including cholangiocarcinoma (CCA). M2 polarization of macrophages is crucial for their biological roles in immunologic tolerance, which is able to induce tumorigenesis. Given that increasing evidence have suggested that lncRNAs could participate in modulating immune cell differentiation and function. Our current study was aimed to identify the underlying mechanism of lncRNA prostate cancer-associated transcript 6 (PCAT6) in CCA progression via regulating M2 macrophage polarization. PCAT6 has been reported as an oncogene in many cancers. In our work, we observed increased expression of PCAT6 in CCA patients. PCAT6 expression in various types of immune cells derived from CCA patients was tested by quantitative real-time PCR (qRT-PCR). It was revealed that PCAT6 was highly expressed in macrophages, which indicated that PCAT6 might regulate the function of macrophages to promote CCA progression. Then, via establishing CCA xenograft mouse model, we found loss of PCAT6 obviously triggered the immune response and reduced the in vivo tumor growth. In addition, overexpression of PCAT6 led to the M2 polarization of THP-1-differentiated macrophages. Moreover, miR-326 was predicted and proved as a target for PCAT6. In addition, down-regulation of PCAT6 repressed M2 polarization of macrophages, which was reversed by miR-326 inhibitors. The increase of PCAT6 induced the accumulation of ROS, mitochondrial and metabolic dysfunction in macrophages and mimics of miR-326 exhibited an opposite process. RohA has been recognized as a significant regulator of immune cell function. In our current work, we observed that RohA function as a downstream target for miR-326. In conclusion, our study highlighted a significant role of PCAT6/miR-326/RohA in immune response of macrophages in CCA and indicated PCAT6 as a potential target of immunotherapy in CCA.